1999
DOI: 10.4141/p98-107
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and environment effect on canning quality of dry bean grown in Saskatchewan

Abstract: . 1999. Genotype and environment effect on canning quality of dry bean grown in Saskatchewan. Can. J. Plant Sci. 79: 335-342. Canning quality traits of dry bean are affected by both the genotype and the environment. This study was conducted to determine the effects of genotype, environment and the genotype × environment interaction on canning quality traits of selected navy bean, black bean and pinto bean cultivars. Three cultivars each of navy bean and black bean and two cultivars of pinto bean were grown at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 11 publications
3
44
0
1
Order By: Relevance
“…In dry bean (Phaseolus vulgaris L.) Ghaderi et al (1984), Hosfield et al (1984) and Balasubramanian et al (1999) reported significant genotype × environment effects for most canning quality traits. Season and season × genotype effects for yield, soaking and several cooking quality traits predominated over genotypic effects .…”
Section: Mots Clésmentioning
confidence: 99%
See 2 more Smart Citations
“…In dry bean (Phaseolus vulgaris L.) Ghaderi et al (1984), Hosfield et al (1984) and Balasubramanian et al (1999) reported significant genotype × environment effects for most canning quality traits. Season and season × genotype effects for yield, soaking and several cooking quality traits predominated over genotypic effects .…”
Section: Mots Clésmentioning
confidence: 99%
“…In dry bean (Phaseolus vulgaris L.) Ghaderi et al (1984), Hosfield et al (1984) and Balasubramanian et al (1999) …”
Section: Mots Clésmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation parameters th~t were employed for canning quality analysis were hydration coefficient (HC), as described by Hosfield and Uebersax (1980), percentage washed drained weight (PWDWT) as described by Balasubramanian et al (1999), and visual appearance (VA), splits, texture, size, clumping and colour as described by Van der Merwe et al (2006b).…”
Section: I Determination Of Canning Q~alitymentioning
confidence: 99%
“…The degree of agglutination of the product is measured by visual assessment and grading that varies on a scale from 1 to 3. The grade 1 is attributed to beans samples that display high agglutination in the bottom of the can, and the grade 3 is attributed to beans samples that display loosened, non-agglutinated grains (BALASUBRAMANIAN et al, 1999).…”
Section: Canned Beans Quality Parametersmentioning
confidence: 99%